LITHUANIAN CAPITAL COMPANY AS A PARTY TO TAX PROCEEDINGS IN POLAND - Bernat, Rafał (Teisė, 2015)
A limited liability company or joint stock company with its headquarters in Lithuania can be a taxpayer of Polish direct or indirect taxes. The Lithuanian company is authorized to be a party to the proceedings before the tax authorities of first or second instance. Since the Polish tax procedure is based on the subjective or objective criterion, there are no obstacles to the proceedings regarding the Lithuanian resident taking place. Note, however, that it must be represented before the authorities by an attorney who uses the Polish language. It is best if this person is a lawyer, legal adviser or tax adviser of Polish origin. If a limited liability company based in Lithuania has its branch in Poland, a person representing a branch may appear before the tax authority. Note, however, that all the repercussions on the course and outcome of the proceedings will affect the parent entity. The fact is that the branch of the company is present in the proceedings in the name and on behalf of the founding company. The lack of current regulations on deliveries in tax proceedings specifically relating to foreign taxpayers should be regarded as a de lege lata application. There is a possibility of delivering the letter by means of electronic communication. However, the taxpayer must already be familiar with complex rules relating to this method of delivery and meet its formal requirements. The need to extend the statutory definition of the taxpayer (located in the Tax Code) with a reference to entities located outside Poland was recognized as a de lege ferenda application. It is worth confirming, through legislative changes, the equality of rights and responsibilities of all taxpayers in the Polish tax procedure, regardless of their residence.